VISUAL BRANDING NAUFAL MAHRI - MUHAMMAD FAHMI, Dr. Syafwandi, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Naufal Mahri is a home-based business that presents a typical Indian snack performed by Syamsi's mother who is located in the city of Padang. This homebased business that was established in 1996 is still standing today, but this home business has not been recognized by indigenous people or indigenous Indonesians because the promotion of the owner only relies on word of mouth promotion. Visual branding has the main function of attracting attention. Making people interested in seeing, then getting to know the brand and finally being able to remember it is the goal of visual branding.The analytical method used in designing visual branding is the method of SWOT analysis. SWOT analysis is an analysis that discusses strength, weakness, opportunities and threats. The design process in designing the visual branding of Naufal Mahri begins with the process of collecting interview data and observing the Naufal Mahri products. The media used in the process of designing Naufal Mahri's visual branding is in the form of primary media, namely packaging and supporting media in the form of papper bags, x-banners, t-shirts, posters, stickers, business cards and key chains. The visual branding design of Naufal Mahri's products aims to make the product better known by the public.Keyword: Branding, India, Snack